The Difficulties Encountered in Teaching English as Foreign Language in The Classroom With Multiple Languages. - Yunita Sari Adelina; Sara Frimaulia; Sakura Alwina (CV. Mitkom Indotama, 2025)
A multilingual person can speak, write, and understand numerous languages. It involves using two or more languages in varied circumstances and purposes. The paper examines multilingual English language teaching problems. The report uses a literature review to compare researchers' opinions. The study article examines multilingual schooling in several countries. Multilingual education advocates also acknowledge their obstacles. Teachers face challenges teaching English in multilingual classes due to linguistic diversity. Due to fear of making mistakes, multilingual students typically lack English confidence. The curriculum may not improve English competence. In multilingual classrooms, language education must be student-centered and take into account learners' needs and backgrounds, according to the study.